On Chlodowsky Variant of (p,q) Kantorovich-Stancu-Schurer Operators - Vishnu Narayan Mishra; Shikha Pandey (International Journal of Analysis and Applications, 2016)
In the present paper, we introduce the Chlodowsky variant of (p,q) Kantorovich-Stancu-Schurer operators on the unbounded domain which is a generalization of (p,q) Bernstein-Stancu-Kantorovich operators. We have also derived its Korovkin type approximation properties and rate of convergence.